Mechanical Metamaterials with Thermoresponsive Switching between Positive and Negative Poisson's Ratios. Issue 5 (28th February 2018) - Park, Haedong; Kwon, Hyungho; An, Yongsan; Yu, Woong‐Ryeol; Moon, Myoung‐Woon; Hur, Kahyun
Abstract : There have been many studies on smart mechanical materials that sensibly deform in response to external stimuli. However, most of the previous studies have focused on structure changes but largely neglected stimuli‐responsive and programmable mechanical properties. Here, we present a novel strategy of mechanical metamaterials, engineered materials with mechanical properties defined by their structure rather than their composition, to design smart materials that change their mechanical properties in response to external stimuli. The present work demonstrates mechanical metamaterials with thermoresponsive and reversible switching between positive and negative Poisson's ratios. In order to realize the thermoresponsive and reversible switching, a thermoresponsive rod with an extremely large thermal expansion coefficient is developed utilizing two‐way shape memory effects. As an application of our metamaterials, we propose soundproofing materials that selectively block sound waves in a specific frequency range depending on temperature. Abstract : A novel strategy for developing smart metamaterials that exhibit programmable mechanical properties in response to external stimuli is proposed. The thermoresponsive behavior is realized by a combination of hexagonal frames and thermoresponsive rods with very large thermal expansion coefficient. These metamaterials can be utilized as soundproofing materials that selectively block sound waves in a specific frequency range depending on temperature.